Study of thermal properties of electronic modules on combined boards with polyimide dielectrics - Borshchov, V.M.; Listratenko, O.M.; Slipchenko, M.I.; Protsenko, M.A.; Tymchuk, I.T.; Kravchenko, O.V.; Borshchov, I.V. (Radiotekhnika, 2024)
This article presesnts the construction and theoretical research of thermal models of electronic modules with increased power based on combined boards on aluminum bases using serial heat-welding polyimide - fluoroplastic films, including films with thermal conductivity from 0.12 to 0.46 W/m•K, as well as with the lacquer foil dielectrics with thermal conductivity of PI layers of the order of 4.0 - 4.5 W/(m•K) improved by the authors Designs and quality test structures of electronic modules were developed. Experimental studies of the efficiency of heat removal from semiconductor devices in quality test structures based on various types of combined boards with polyimide dielectrics were performed. Technical solutions of combined boards based on multi-layer heat-conductive heat-welding PMF film Kapton®120FMT616 30 μm thick with fluoropolymer double-sided coatings with a thermal conductivity of 0.46 W/(m•K) and combined circuit boards based on improved one-sided lacquer foil copper - polyimide dielectrics with a thickness of highly thermally conductive composite PI layers 60 μm with a thermal conductivity of up to 4.0 - 4.5 W/(m•K), provided under favorable operating conditions with natural unobstructed convection and temperature environment Ta = 25oС the best thermal characteristics of electronic modules from the point of view of maintaining recommended operating temperatures < 70 – 80 °C for high reliability of operation and increased service life.